2005
DOI: 10.1163/156856005774423971
|View full text |Cite
|
Sign up to set email alerts
|

Role of central and peripheral ghrelin in the mechanism of gastric mucosal defence

Abstract: Ghrelin, identified in the gastric mucosa, has been involved in the control of food intake and growth hormone (GH) release, but whether this hormone influences the gastric secretion and gastric mucosal integrity has been little elucidated. We compared the effects of intraperitoneal (i.p.) and intracerebroventricular (i.c.v.) administration of ghrelin on gastric secretion and gastric lesions induced in rats by 75% ethanol or 3.5 h of water immersion and restraint stress (WRS) with or without suppression of nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 34 publications
1
36
0
4
Order By: Relevance
“…On the basis of a C-terminal Gly-Lys motif, amidation of obestatin was assumed and verified as a prerequisite for biological activity [162]. Furthermore, the mass spectrometric data indicated that this peptide may be processed to a 13 amino acid peptide, obestatin (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Further information is required to establish exactly how obestatin (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) is formed, although, a recent study indicates that this isoform is indeed biologically active [62].…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of a C-terminal Gly-Lys motif, amidation of obestatin was assumed and verified as a prerequisite for biological activity [162]. Furthermore, the mass spectrometric data indicated that this peptide may be processed to a 13 amino acid peptide, obestatin (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Further information is required to establish exactly how obestatin (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) is formed, although, a recent study indicates that this isoform is indeed biologically active [62].…”
Section: 3mentioning
confidence: 99%
“…Indeed, a gastroprotective effect has been demonstrated in various models, which seems to depend mainly on vagal activity, sensory nerves and hyperaemia mediated by nitric oxide synthase-nitric oxide (NOS-NO) and cyclooxygenase-prostaglandin systems [15,16]. The protective effect has also been demonstrated in experimental colitis [57].…”
Section: Gastrointestinal Functionmentioning
confidence: 99%
“…amylin, adrenomedullin, neurotensin, opioid peptides, melatonin, ghrelin, leptin, as well as cannabinoids were shown to initiate gastroprotective effect given centrally (i.c.v., i.c. or DMNV), mostly by a vagal dependent mechanism [139][140][141][142] (see reviews: [4,127,138,143,144]). …”
Section: Role Of Capsaicin Sensitive Afferent Fibers and In The Actiomentioning
confidence: 99%
“…Other hormone mediators, including gastrin-17, cholecystokinin, thyrotropin-releasing hormone, bombesin, EGF, peptide YY and neurokinin A, play significant roles in the regulation of gastric protective mechanisms, which can be blunted by afferent nerve ablation, CGRP receptor blockade, and inhibition of NO synthase (Peskar, 2001;Moszik et al, 2001). Ghrelin, a hormone peptide produced by gastric A-like cells in rodents and P/D1 cells in humans, is involved in the regulation of growth hormone secretion and appetite stimulation (Brzozowski et al, 2005b). Moreover, it is also able to exert significant protective effects at gastric level, including the enhancement of mucosal blood flow via stimulation of NO and CGRP release from sensory afferent nerves (Brzozowski et al, 2005b).…”
Section: Neurohormonal Mechanismsmentioning
confidence: 99%